Comparative evaluation of audio and audio - tactile methods to improve oral hygiene status of visually impaired school children - R Krishnakumar; Swarna Swathi Silla; Sugumaran K Durai; Mohan Govindarajan; Syed Shaheed Ahamed; Logeshwari Mathivanan (Wolters Kluwer Medknow Publications, 2016)
Background: Visually impaired children are unable to maintain good oral hygiene, as their tactile abilities are often underdeveloped owing to their visual disturbances. Conventional brushing techniques are often poorly comprehended by these children and hence, it was decided to evaluate the effectiveness of audio and audio-tactile methods in improving the oral hygiene of these children. Objective: To evaluate and compare the effectiveness of audio and audio-tactile methods in improving oral hygiene status of visually impaired school children. Materials and Methods: In this study, the total study group comprised 48 visually impaired children that were randomly divided into two groups, with one group receiving the audio method and the other group receiving the audio-tactile method. Periodic reinforcement of health education was performed at an interval of 2 months. Re-examination was carried out after 2 months of health education to assess plaque scores. Data were statistically analyzed using paired t-test. Results: There was reduction in plaque scores in audio-tactile group after health education. In the audio-tactile group, the mean plaque scores of pre- and post-health education were 1.28 and 0.95, respectively. The difference was statistically significant (P < 0.001). In audio group, the mean plaque scores of pre- and post-health education were 1.15 and 0.14, respectively. The difference was statistically nonsignificant (P < 0.07). Conclusion: Visually impaired children could maintain an acceptable level of oral hygiene when taught using special customized methods. However, reinforcement at regular intervals is required for the maintenance of oral hygiene.